2021
DOI: 10.3390/land10080848
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Compactness of Urban Growth on Regional Landscape Ecological Security

Abstract: With rapid urbanization destroying the ecological environment, scholars have focused on ways to coordinate harmonious development using urban spatial layouts and landscape ecological security. To explore landscape ecological security (the landscape elements, spatial positions and connections that are of key significance to the health and safety of ecological processes) from the perspective of urban form evolution pattern will help to open a new perspective of urban management research, and become the basic wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…In China, significant differences in socio-economic development and natural conditions among regions have caused the factors influencing ES in different regions to vary [12,17,22,26,[72][73][74][75] (Figure 9). For the border areas in Yunnan Province, we found that the fixed asset investment, per capita fiscal revenue, per capital GDP, and food production are the main factors creating obstacles to improving the level of ES, which is consistent with previous research results [73].…”
Section: Discussion On Obstacle Factorsmentioning
confidence: 99%
“…In China, significant differences in socio-economic development and natural conditions among regions have caused the factors influencing ES in different regions to vary [12,17,22,26,[72][73][74][75] (Figure 9). For the border areas in Yunnan Province, we found that the fixed asset investment, per capita fiscal revenue, per capital GDP, and food production are the main factors creating obstacles to improving the level of ES, which is consistent with previous research results [73].…”
Section: Discussion On Obstacle Factorsmentioning
confidence: 99%
“…For example, Zhou et al (2014) used the following five landscape metrics to reflect ecological security: patch density, mean shape index, area-weighted mean patch fractal dimension, contagion, and Shannon's diversity index, each of which represents a different landscape characteristic. Similarly, Rao et al (2021) used both class-level metrics (percentage of patch type, shape index, and patch density) and landscapelevel metrics (mean patch area, edge density, aggregation index, and diversity index).…”
Section: Spatial Analysis Methodsmentioning
confidence: 99%
“…The key factors affecting ecological security were identified by the Geo-detector, a tool that can reveal the driving factors of stratified spatial heterogeneity. Based on the geographically weighted regression model, Rao et al (2021) analyzed the impact of urban growth patterns (characterized by elevation, population density, and gross domestic product) on ecological security (characterized by landscape indices).…”
Section: Correlation Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Suburbanization is a factor that affects the expansion of urban areas to suburban areas causing changes in spatial patterns due to increased development activities [8,9]. Thus, it is necessary to regulate the use of space and the allocation of landscape resources in a reasonable manner in order to achieve environmental balance towards sustainable development [10,11].…”
Section: Introductionmentioning
confidence: 99%